Be patient when measuring hyperbolic discounting: Stationarity, time consistency and time invariance in a field experiment - Janssens, Wendy; Kramer, Berber; Swart, Lisette (Elsevier, 2017)
Hyperbolic discounting is one potential reason why savings remain low among the poor. Most evidence of hyperbolic discounting is based on violations of either stationarity or time consistency. Stationarity is violated when intertemporal choices differ for trade-offs in the near versus the more distant future. Time consistency is violated if the optimal allocation for specific dates changes over time. Both types of choice reversals may however also result from time-varying discount rates. Hyperbolic discounting is an unambiguous explanation for choice reversals only if the same individuals violate both stationarity and time consistency. Our field experiment in Nigeria examines the extent to which this is the case. The experiment measured both stationarity and time consistency for the same participants. Violations of the two rarely coincide, especially among more liquidity-constrained participants. Thus, in a context of liquidity constraints, eliciting only one type of choice reversal is insufficient to identify hyperbolic discounting.